Diffusion Tractography Biomarkers of Pediatric Cerebellar Hypoplasia/Atrophy: Preliminary Results Using Constrained Spherical Deconvolution - Fiori, S.; Poretti, A.; Pannek, K.; Del Punta, R.; Pasquariello, R.; Tosetti, M.; Guzzetta, A.; Rose, S.; Cioni, G.; Battini, R. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Advances in MR imaging modeling have improved the feasibility of reconstructing crossing fibers, with increasing benefits in delineating angulated tracts such as cerebellar tracts by using tractography. We hypothesized that constrained spherical deconvolution–based probabilistic tractography could successfully reconstruct cerebellar tracts in children with cerebellar hypoplasia/atrophy and that diffusion scalars of the reconstructed tracts could differentiate pontocerebellar hypoplasia, nonprogressive cerebellar hypoplasia, and progressive cerebellar atrophy.MATERIALS AND METHODS: Fifteen children with cerebellar ataxia and pontocerebellar hypoplasia, nonprogressive cerebellar hypoplasia or progressive cerebellar atrophy and 7 controls were included in this study. Cerebellar and corticospinal tracts were reconstructed by using constrained spherical deconvolution. Scalar measures (fractional anisotropy and mean, axial and radial diffusivity) were calculated. A general linear model was used to determine differences among groups for diffusion MR imaging scalar measures, and post hoc pair-wise comparisons were performed.RESULTS: Cerebellar and corticospinal tracts were successfully reconstructed in all subjects. Significant differences in diffusion MR imaging scalars were found among groups, with fractional anisotropy explaining the highest variability. All groups with cerebellar pathologies showed lower fractional anisotropy compared with controls, with the exception of cerebellar hypoplasia.CONCLUSIONS: This study shows the feasibility of constrained spherical deconvolution to reconstruct cerebellar and corticospinal tracts in children with morphologic cerebellar pathologies. In addition, the preliminary results show the potential utility of quantitative analysis of scalars of the cerebellar white matter tracts in children with cerebellar pathologies such as cerebellar hypoplasia and atrophy. Further studies with larger cohorts of patients are needed to validate the clinical significance of our preliminary results.ADaxial diffusivityCAprogressive cerebellar atrophyCHnonprogressive cerebellar hypoplasiaCPCTcorticopontocerebellar tractCSTcorticospinal tractCTTcerebellar-thalamic tractdMRIdiffusion MR imagingFAfractional anisotropyMDmean diffusivityPCHpontocerebellar hypoplasiaRDradial diffusivity